Covid-19: How is the Sharia Hospitality Industry and Health Industry Survive in Indonesia? - Insawan, Husain; Alwahidin, Alwahidin; Santri, Dewi (International Journal of Transdisciplinary Knowledge, 2021)
Fama & French explained that company size affects the risk of return on its shares. The larger the size of a company, the more established the company is.Hence, it is not easily swayed by crisis pressures, not only financial pressure but also social pressure. The Covid-19 outbreak hitting the world, especially Indonesia, also had an impact on performance in the capital market. The test results showed that during the Covid-19 outbreak period, the JCI performance decreased by 30 percent. However, further test results showed that the hotel and resort industry did not necessarily show worse performance. Moreover, the results of the panel data regression test using data from 16 companies and 29 weeks period of timeshowed that during the period of the Covid-19 pandemic outbreak in Indonesia from March to June, although it is not statistically significant, the performance of the hotel and resort industry outperforms the health industry, while the performance of the Islamic stock category for the two industries is outperformed by the performance of its alternative stocks. The results of this test strengthen the three-factor model Fama & French as well as the five-factor model Fama & French that companies with large assets in the hotel and resort industry included in the research sample are able to withstand the impact of the Covid-19 pandemic, beating companies which are inferior in terms of company size such as the healthcare industry in Indonesia.